Assessment of genotypic variability and genome‐wide association analysis of cooking time and canning quality traits in common bean (Phaseolus vulgaris L.) - Kesiime, Eunice Vasiter; Nkalubo, Stanley Tamusange; Ochwo Ssemakula, Mildred; Dramadri, Isaac Onziga; Mukankusi, Clare; Nakimbugwe, Dorothy; Edema, Richard; Gibson, Paul; Badji, Arfang (Wiley, 2024)
Developing improved common bean varieties with short cooking time (CT) and good canning quality traits (CQTs) is very key for accelerating bean consumption among the urban and middle‐class population. The objective of this study was to assess the genotypic variability and identify single nucleotide polymorphism (SNP) markers associated with CT and CQTs in common bean. A total of 250 common bean accessions were evaluated under field conditions for two seasons using alpha lattice design with two replications. Three months post‐harvest, the dry bean grains were evaluated for CT and CQTs. Significant variation was observed among the 250 common bean accessions tested for both traits. CT ranged from 51 to 215 min, with 11 genotypes cooking in less than 60 min. The percentage total CQTs' score ranged from 41% to 84% with 31 genotypes scoring 76% and above. Forty‐seven significant GWAS signals were detected for CT on chromosomes Pv01, Pv04, Pv05 and Pv11 and CQTs on Pv01, Pv02, Pv03, Pv04, Pv05, Pv06, Pv07, Pv08, Pv10 and Pv11, respectively. Positional candidate genes including Phvul.005G161200 on chromosome Pv05, Phvul.007G2803001 and Phvul.007G280700 on chromosome Pv07 were associated with seed coat colour retention of the canned beans. Besides their usefulness in breeding research, the identified bean genotypes with shorter CT and good CQTs could enhance bean consumption and processing industries.